Four new species of Cerambycidae (Coleoptera) from Paraguay - Mehl, Ole (Zookeys, 2015)
Abstract. Four new species of Cerambycidae are described from Paraguay: Eranina tomentilla (Hemilophini); Mimasyngenes concolor (Desmiphorini); Recchia drechseli (Aerenicini); and Microibidion bimaculatum (Neoibidionini). The new species are included in known keys.